2022
DOI: 10.1242/jeb.243225
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytic approaches and effect sizes to account for ‘nuisance heterogeneity’ in comparative physiology

Abstract: Meta-analysis is a powerful tool used to generate quantitatively informed answers to pressing global challenges. By distilling data from broad sets of research designs and study systems into standardised effect sizes, meta-analyses provide physiologists with opportunities to estimate overall effect sizes and understand the drivers of effect variability. Despite this ambition, research designs in the field of comparative physiology can appear, at the outset, as being vastly different to each other because of ‘n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Most published papers today provide useable data, but it is still relatively common for data to be shared in an unusable format. For example, when surveying the meta-analyses in comparative physiology identified by Noble et al (2022;this issue), only 70% (37) of the 53 papers that provided data did so in a useable format and 30% ( 16) did so with an unusable format. Similarly, around 64% of data archives in ecology and evolution are not usable (Roche et al, 2015).…”
Section: Tip 3: Version Control Your Databasementioning
confidence: 99%
See 3 more Smart Citations
“…Most published papers today provide useable data, but it is still relatively common for data to be shared in an unusable format. For example, when surveying the meta-analyses in comparative physiology identified by Noble et al (2022;this issue), only 70% (37) of the 53 papers that provided data did so in a useable format and 30% ( 16) did so with an unusable format. Similarly, around 64% of data archives in ecology and evolution are not usable (Roche et al, 2015).…”
Section: Tip 3: Version Control Your Databasementioning
confidence: 99%
“…studies of mass-corrected traits that do not present mass) might be problematic. In this sense, tools like the R packages Rphylopars (Goolsby et al, 2017) and mice (van Buuren and Groothuis- Noble et al (2022;this issue)] that clearly reported sample sizes, the percentage of primary studies included (orange) and discarded (blue) after the first (title and abstract) and second (full-text) screenings. The black line represents the minimum and maximum of the percentage of studies included across all 29 meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors provide practical approaches to maximising the efficiency and accessibility of comparative databases, which in turn helps to promote and ensure data transparency and integrity. Daniel Noble and co-workers (Noble et al, 2022) also provide a very useful guide to dealing with 'nuisance heterogeneity' in comparative physiology meta-analysis, offering a way forward to compare data across studies even when, for example, temperatures or dosages are different.…”
mentioning
confidence: 99%